(untitled) (Research, Society and Development, 2020)
The main objective of this work is to characterize the academic production on experimentation and its possible contributions in the teaching of Sciences. The methodology used consisted of conducting research in theses and dissertations bank of Brazilian universities in postgraduate programs with concepts 5 to 7, according to Capes’ evaluation, in the area of Science Education. The research adopted as period of time the period from 2008 to 2017 and resulted in a total of 52 theses and dissertations that approached the thematic experimentation. The scientific production in the studied period showed that Physics was the area that produced the most works with thematic experimentation, followed by Chemistry, Biology and Sciences, respectively. Among the categories established to evaluate the contributions considered by the researchers regarding the use of experimental activities in science teaching, the use of experimentation to apprehend scientific concepts and improve teaching practice stands out.